THE INFLUENCE OF VENTURE CAPITAL, ONLINE TRANSACTIONS, SUBJECTIVE NORMS, ENTREPRENEURSHIP EDUCATION PROGRAMS, ON ENTREPRENEURSHIP INTENTION - Budiningrum, Endah Wening; Subandi, Subandi; Kurnianingsih, Retno (Universitas Negeri Yogyakarta, 2024)
The digitalization era can actually make it easier for aspiring entrepreneurs to start a business. Contrary to this, access to financing is not in accordance between government recommendations and reality in the field, where the government exempts collateral for businesses that are just starting out, while the financing channel requires a minimum business age of one year and certain collateral as reinforcement. So that most students still have a mindset as job seekers rather than creating jobs themselves, even though entrepreneurship education programs have been carried out at every level of education.Therefore, this study aims to determine the direct or indirect effect between business capital, digital transactions, subjective norms on student entrepreneurial intentions. The results of this study are expected to contribute to how entrepreneurship education programs should be made so that students' entrepreneurial intentions can be created. This study tested 158 samples from students of the Yogyakarta Academy of Administrative Management with hypothesis testing in this study using SEM (Structural Equation Modeling). The SEM analysis tool used is SEM PLS (Partial Least Squares) WarpPLS 7.0.The results obtained from this study are business capital and online transactions do not have a direct influence on entrepreneurial intentions. While subjective norms and entrepreneurship education programs have a direct influence on entrepreneurial intentions. Indirect influence occurs between venture capital, onlilne transactions, subjective norms to entrepreneurial intentions, as well as when through entrepreneurship education programs. Students' intentions for entrepreneurship arise when they have capital and also know how to transact online and there is support from the immediate environment and are trained in entrepreneurship education programs. For this reason, in entrepreneurship learning, training must be provided that combines capital, transactions and training programs as well as motivation from the closest people to create new entrepreneurs.